2. Yacimientos uraníferos. 1. Geoquímica del uranio - Nicolli, Hugo B.; Gamba, Mirtha Ana (Comisión Nacional de Energía Atómica; Argentina, 1978)
Fil: Gamba, Mirtha Ana. Comisión Nacional de Energía Atómica; Argentina